Succession of the microbiota in the gut of reproductives of Macrotermes subhyalinus (Termitidae) at colony foundation gives insights into symbionts transmission - Diouf, Michel; Hervé, Vincent; Fréchault, Sophie; Lambourdière, Josie; Ndiaye, Abdoulaye Baïla; Miambi, Edouard; Bourceret, Amélia; Jusselme, My Dung; Selosse, Marc-André; Rouland-Lefèvre, Corinne (Frontiers in Ecology and Evolution, 2023)
Termites have co-evolved with a complex gut microbiota consisting mostly of exclusive resident taxa, but key forces sustaining this exclusive partnership are still poorly understood. The potential for primary reproductives to vertically transmit their gut microbiota (mycobiome and bacteriome) to offspring was investigated using colony foundations from field-derived swarming alates of Macrotermes subhyalinus. Metabarcoding based on the fungal internal transcribed spacer (ITS) region and the bacterial 16S rRNA gene was used to characterize the reproductives mycobiome and bacteriome over the colony foundation time. The mycobiome of swarming alates differed from that of workers of Macrotermitinae and changed randomly within and between sampling time points, highlighting no close link with the gut habitat. The fungal ectosymbiont Termitomyces was lost early from the gut of reproductives, confirming the absence of vertical transmission to offspring. Unlike fungi, the bacteriome of alates mirrored that of workers of Macroterminae. Key genera and core OTUs inherited from the mother colony mostly persisted in the gut of reproductive until the emergence of workers, enabling their vertical transmission and explaining why they were found in offspring workers. These findings demonstrate that the parental transmission may greatly contribute to the maintenance of the bacteriome and its co-evolution with termite hosts at short time scales.